Pengaruh Financial Stability, Financial Target, Nature Of Industry,dan Auditor Switch Terhadap Financial Statement Fraud - Ariyana Hermawati; Dwiyanjana Santyo Nugroho (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This research was conducted with the aim of determining the influence of financial stability, financial targets, nature of industry, and auditor switching on financial statement fraud. This research is quantitative research with the data used in the form of secondary data from company financial reports. The objects used in this research are state-owned companies registered on the BEI from 2019 to 2022. The samples obtained in this research were 27 companies so that the total sample used was 108. Data analysis was carried out using descriptive statistics, classical assumption tests, determination analysis , and multiple linear regression analysis. The research results show that financial stability and financial targets have a significant effect on financial statement fraud, while the nature of industry and auditor switching have no effect on financial statement fraud.